Calcifying Fibrous Tumor: Review of 157 Patients Reported in International Literature. Issue 20 (May 2016) - Chorti, Angeliki; Papavramidis, Theodossis S.; Michalopoulos, Antonios
Abstract : Abstract: Calcifying fibrous tumor (CFT) is a benign lesion characterized by its specific histological findings and is found as solitary or multiple lesions in several locations of the human body. The aim of the present systematic review is to give a detailed account of all reported cases of CFT in the literature and to analyze the available data, to completely characterize the entity from epidemiological, medical, and surgical aspects. A bibliographic research was performed from 1988 until 2015. A database with the patients' characteristics was made, including sex, age, location of the tumor, symptoms, symptoms duration, size of the tumor, diagnostic methods, treatment, metastasis, and follow-up. A total of 104 articles were identified, reporting 157 cases of CFT. Mean age of patients was 33.58 years and the ratio between men and women was 1:1.27. The most common locations of CFT were stomach (18%), small intestine (8.7%), pleura (9.9%), mesentery (5%), and peritoneum (6.8%). Mean diameter of the tumor was estimated 4.6 cm. The correlations proceeded showed that as age increases, size decreases ( P = 0.001) and that the tumor is larger in females ( P = 0.027). Kruskal-Wallis test showed that the larger tumors appear in the neck and adrenal gland ( P = 0.001). The percentage of asymptomatic patients was 30.57%. Computed tomography and biopsy were the most common tests for the diagnosis of CFT. Open surgical procedure was performed in the majority of cases. The median hospitalization was 6.06 days and the mean follow-up period was 29.97 months. Recurrences were mentioned in 10 of 96 patients with available data. No deaths owing to CFT were mentioned in the literature. CFT should be included in the differential diagnosis of enlarging mass revealed by clinical or imaging examination either incidentally or after specific acute or chronic symptomatology.